(untitled) (ENTHYMEMA, 2019)
Translation of: Taccetta, Natalia, “Signatura e historia: una aproximación al encuentro Benjamin-Agamben”, Metahistorias, 2011. The aim of this article is to discuss the relation between Benjamin and Agamben in defining the Avant-guard as aesthetic and cognitive phenomenon.